Evaluating lean production requirements in Syrian industrial companies - a case study in Barada Electrical and Household Industries Company. (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
This study aimed to evaluate the lean production requirements at Barada Electrical and Home Industries Company. It addressed lean production tools: cellular manufacturing, rapid setup and changeover, just-in-time production, continuous improvement, workplace organization, and total production maintenance. The study used a questionnaire as the primary data collection tool.The study sample consisted of (30) workers in Barada Company, Use SPSS software to analyze the data, and the results of the study were: the use of lean production tools in Barada Company for Electrical and Home Industries, The highest approval ratings were for Total Productive Maintenance and workplace organization, which confirms that the company pays great attention to preventive maintenance programs for machinery and equipment, in addition to improving the internal arrangement and organization of those machines. The lowest approval ratings were for on-time production,The company does not simply produce what the customer orders. The study suggested: continued investment in lean production tools, flexibility to meet varying quantity needs and delivery speeds, a strategic vision for full employee engagement, and the provision of training courses.
Keywords: Lean production, cellular manufacturing, rapid setup and changeover, just-in-time production.